2016
DOI: 10.1038/srep39630
|View full text |Cite
|
Sign up to set email alerts
|

PRKAR1A is a functional tumor suppressor inhibiting ERK/Snail/E-cadherin pathway in lung adenocarcinoma

Abstract: Protein Kinase cAMP-Dependent Regulatory Type I Alpha (PRKAR1A) is a tissue-specific extinguisher that transduces a signal through phosphorylation of different target proteins. Loss of PRKAR1A was frequently observed in endocrine neoplasia and stromal cell tumors. However, a few cases were seen in epithelial tumors. Previously, we first found that PRKAR1A was downregulated in lung adenocarcinoma patients. Thus, the present study aimed to clarify its clinical implication and biological function as a tumor suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…Accordingly, several RET fusion partners have been shown to exert relevant homeostatic functions (Table 1). PRKAR1A, one of the RET fusion partners, is the tumor suppressor protein involved in inheritance of Carney complex, a tumor-prone syndrome [90]. Similarly, another RET fusion partner, NCOA4, is a multifunctional protein that is involved in the regulation of DNA synthesis by inhibiting replication origin activation.…”
Section: Functional Consequence Of Ret Gene Fusionsmentioning
confidence: 99%
“…Accordingly, several RET fusion partners have been shown to exert relevant homeostatic functions (Table 1). PRKAR1A, one of the RET fusion partners, is the tumor suppressor protein involved in inheritance of Carney complex, a tumor-prone syndrome [90]. Similarly, another RET fusion partner, NCOA4, is a multifunctional protein that is involved in the regulation of DNA synthesis by inhibiting replication origin activation.…”
Section: Functional Consequence Of Ret Gene Fusionsmentioning
confidence: 99%
“…Reports have shown that Prkar1a knockout increases PKA activity, as well as resistance to apoptosis via mTOR activation (Robinson-White et al, 2006;Pringle et al, 2014). Additionally, it has also been shown that Prkar1a regulates the ERK, Snail and E-cadherin pathways (Wang et al, 2016). We investigated the mechanistic mechanisms of Prkar1a in cancer cells, showing that its genetic perturbation leads to drastic alterations in the proteome, phosphoproteome, and the transcriptome.…”
Section: Discussionmentioning
confidence: 97%
“…In this context, hereditary or germline LOF mutations in Prkar1a were sufficient to produce the disease in a dominant manner. In addition, Prkar1a mutations are associated with several tumor types such as cardiac, endocrine, thyroid, and lung adenocarcinoma (Kondo et al, 2017;Wang et al, 2016) (Saloustros et al, 2017). Prkar1a overexpression is also associated with tumor formation in multiple contexts, indicating that altering Prkar1a function leads to differential phenotypes across cellular and genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were randomly divided into groups ( n = 5 per group) before injection. The invasion effect of SH2B1 on LADC progression was examined in a lung colonization model . Two groups were injected with shSH2B1 transduced A549 cells or control A549 cells (1 × 10 6 cells in 0.1 ml phosphate‐buffered saline) via lateral tail veins.…”
Section: Methodsmentioning
confidence: 99%
“…The invasion effect of SH2B1 on LADC progression was examined in a lung colonization model. 42 Two groups were injected with shSH2B1 transduced A549 cells or control A549 cells (1 × 10 6 cells in 0.1 ml phosphate-buffered saline) via lateral tail veins. Another two groups were intravenously injected with stable SH2B1-overexpressing or control H1299 cells.…”
Section: Xenografted Tumor Model and Hande Stainingmentioning
confidence: 99%